2004
DOI: 10.1063/1.1713025
|View full text |Cite
|
Sign up to set email alerts
|

Local conductivity and surface photovoltage variations due to magnesium segregation in p-type GaN

Abstract: Conductive atomic force microscopy ͑C-AFM͒ and surface photovoltage ͑SPV͒ microscopy were used to investigate local electronic structure in p-type GaN. C-AFM imaging revealed locally reduced forward-and reverse-bias conductivity near threading dislocations. In addition, regions near threading dislocations demonstrated significantly enhanced surface photovoltage response when compared to regions away from dislocations. Analytical treatment of the surface photovoltage as a function of pertinent material properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…This result is in contrast to the experiments performed on sample A with the n-doped top layer but it is in agreement with similar experiments performed by Simpkins et al on p-GaN. 11 In fact, the current maxima, indicated by the dark areas, occur outside the regions of the V-defects. Increasing the applied voltage further, the current flow across the structure becomes stronger in particular areas outside the V-defects ͑not shown͒.…”
Section: Electrical Investigation Of V-defects In Gan Using Kelvin Prsupporting
confidence: 72%
See 1 more Smart Citation
“…This result is in contrast to the experiments performed on sample A with the n-doped top layer but it is in agreement with similar experiments performed by Simpkins et al on p-GaN. 11 In fact, the current maxima, indicated by the dark areas, occur outside the regions of the V-defects. Increasing the applied voltage further, the current flow across the structure becomes stronger in particular areas outside the V-defects ͑not shown͒.…”
Section: Electrical Investigation Of V-defects In Gan Using Kelvin Prsupporting
confidence: 72%
“…7,10 In contrast, other authors found a decrease in current within the V-defects for p-doped samples. 11 A rich diversity of explanations, including the formation of oxide layers with spatially varying thickness, 10 an indiffusion of the contact material along the dislocations 12 or a decrease in the electrically active doping materials within the V-defect due to segregation 11 have been suggested in order to explain the experimental results. Still, a consistent picture explaining both the local potential and the local current measurements of a V-defect in n-and in p-doped GaN heterostructures is missing.…”
Section: Electrical Investigation Of V-defects In Gan Using Kelvin Prmentioning
confidence: 99%
“…This has the important consequence of obtaining high-Al-content Al 0.77 Ga 0.23 N doped layers of pit-free surface morphology and retained transport properties. Admittedly, 21 the formation of pits-caused by the raised Si doping level especially under the conditions of enhanced growth rate-entails high resistivity. The layer T4 in Fig.…”
mentioning
confidence: 99%
“…KPFM has been used to measure surface (contact) potentials [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] as a function of polarity, doping and surface treatment, surface band bending [22], and bare surface barrier heights [24] of III-nitrides. The measurement of these electronic properties is critical for designing devices based on III-nitrides.…”
Section: Characterization Of Surface Electronic Properties By Spmmentioning
confidence: 99%
“…They employed scanning capacitance microscopy (SCM) to investigate threading dislocations in GaN. Since then, SCM [13][14][15], electrostatic force microscopy (EFM) [16][17][18][19][20], Kelvin probe force microscopy (KPFM) [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36],conductive-tip atomic force microscopy (C-AFM) [35][36][37][38][39][40][41][42][43][44][45][46], piezoresponse force microscopy (PFM) [47][48][49][50] and scanning gate microscopy (SGM) [51] have all been employed to characterize III-nitride films and surfaces.…”
Section: Introductionmentioning
confidence: 99%